ACCOUNTING INSTRUCTION AT IOWA. - Winter, S. G. (The Accounting Review, 1927)
The article discusses the aim and method of accounting instruction in the State University of Iowa. The university has a two-year college of commerce, and, accordingly, the majority of the students are university juniors and seniors. First-year accounting work is offered, however, to pre-commerce sophomores who are technically students in the College of Liberal Arts. This work is entirely under the control of the College of Commerce and is placed in the sophomore year primarily to enable the student to secure some business background before coming in contact with commerce work proper. In other words university believes that a knowledge accounting principles is a desirable factor in the background which will enable the commerce student to make the most out of his two years in the College of Commerce. This course is prescribed for all commerce students. There is a "raison d'etre" for first-year work in accounting. University's experience has convinced it that the student's contact with the principles course in accounting furnishes him with a knowledge of business terms, procedures, and results which will aid him materially in mastering such counts as corporation finance, money and banking, industrial management etc.